From Analogue to Virtual: Urban Interiors in the Pandemicene - Hinkel, Rochus Urban (Interiority, 2020)
This paper speculates on the potential long-term impact of the COVID-19 pandemic on the way we interact with each other in cities by focusing on the socio-spatial concept of the urban interior. How will our everyday life in cities change? What changes will be wrought on our informal encounters and our temporal occupation of places and spaces? What impact will future urban planning have on the way we move through, work and study in and act as individuals and collectives in our cities? In order to look ahead, it is worth reflecting on historical examples. Studying the ways diseases have influenced how we shape and design, control and govern, explore and occupy urban environments suggests that we will likely have to rethink of our cities in anticipation of future pandemics. No doubt, post-COVID-19, we will witness changes in urban politics with consequences in urban planning and design. We will see a continued impact on an informal level too, on how people interact and what sort of individual and shared activities they will engage with. Will public space become increasingly controlled, politicised or irrelevant for political expression? It is clearly too early to come to a conclusion, but based on the past and based on observations of already emerging spatial practices in urban settings, we can speculate upon what kinds of futures might emerge.